2017
DOI: 10.1016/j.ajme.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Gold in semen: Level in seminal plasma and spermatozoa of normal and infertile patients

Abstract: The study was conducted to understand the amount of gold in semen of normal and different infertile conditions. Gold was estimated in normal (n38) and pathological conditions (n86) by employing Atomic Absorption Spectrophotometer. Gold level observed in seminal plasma was as follows: in normozoospermia (n38)-17.0 lg% ± 9.63; oligozoospermia (n23)-13.0 lg% ± 0.73; oligoasthenozoospermia (n44)-20.5 lg%5 ± .58 and in azoospermia (n19) 21.5 lg% ± 7.52. Gold level in sediment (spermatozoa) of normal was almost same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Results of different studies in seminal plasma of normal and pathological samples showed gold as an essential element for fertility. 13,21 In this study, we observed weight gain of animals in study group (SB) which may be due to increased androgen level (Table 1). The ratio of the relative weight of testes with body weight was almost identical in both groups.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Results of different studies in seminal plasma of normal and pathological samples showed gold as an essential element for fertility. 13,21 In this study, we observed weight gain of animals in study group (SB) which may be due to increased androgen level (Table 1). The ratio of the relative weight of testes with body weight was almost identical in both groups.…”
Section: Discussionmentioning
confidence: 54%
“…The locations of entry are likely to be caput epididymis and prostate gland 14 . Histochemicaly gold particles were shown on the rim of seminiferous tubule 21 . Results of all studies lead to the conclusion that gold is present in the fluid medium of male genital system and is essential for sperm motility.…”
Section: L-64mentioning
confidence: 95%
“…This was supported by earlier reports. 37,89,71 Each element may have a specific role to play in life of a sperm cell. 74 Results of studies conducted by different groups of workers proved this.…”
Section: Discussionmentioning
confidence: 99%
“…The element gold is proved as important for fertility. 89 Its role was known to Ayurveda, a traditional medicine, widely used in India and other Asian countries,. In many cases of male infertility, physicians in Ayurveda prescribed gold in the form of its ash, "Suvarna Bhasma" (SB) (Gold Ash).…”
Section: Discussionmentioning
confidence: 99%